Six Weeks of Basketball Combined With Mathematics in Physical Education Classes Can Improve Children's Motivation for Mathematics - Wienecke, Jacob; Hauge, Jesper; Nielsen, Glen; Mouritzen, Kristian; Damsgaard, Linn (Frontiers in Psychology, 2021)
This study investigated whether six weeks of basketball combined with mathematics once a week in physical education lessons could improve children’s motivation for mathematics. 757 children (mean age = 10.36 years ± 0.4) were randomly selected to have either basketball combined with mathematics once a week (BM), or to have basketball sessions without mathematics (CON). Children in BM and CON motivation for classroom-based mathematics was measured using the Academic Self-Regulation Questionnaire (SRQ-A) before (T0) and after the intervention (T1). Among BM levels of intrinsic motivation, feelings of competence and autonomy were measured using the Post-Experimental Intrinsic Motivation Inventory (IMI) questionnaire acutely after a basketball session combined with mathematics and immediately after a session of classroom-based mathematics. BM had significantly higher acute levels of perceived autonomy (+14.24 %, p < 0.0001), competencies (+6.33 %, p < 0.0001) and intrinsic motivation (+16.09 %, p < 0.0001) during basketball sessions combined with mathematics compared to when having classroom-based mathematics. A significant decrease in mean for intrinsic motivation was observed from T0 to T1 for CON (-9.38 %, p < 0.001), but not for BM (-0.39 %, p = 0.98). BM had a more positive development in intrinsic motivation compared to CON from T0 - T1 (p = 0.006), meaning that BM had a positive influence on children’s intrinsic motivation for classroom-based mathematics. This study indicates that basketball combined with mathematics is an intrinsically motivating way to practice mathematics, which also has a positive influence on children’s general intrinsic motivation for mathematics in the classroom.